Social Comparison Inside Business Groups and Strategic Change: Evidence from Group‐affiliated Chinese Firms - Ma, Pengcheng; Cui, Lin; Xu, Dean (Journal of Management Studies, 2024)
AbstractThis study examines the effect of performance feedback on strategic change with a focus on internal social comparison in a business group context. We argue that group affiliates are more responsive to internal social comparison with group peers than to external social comparison with industry peers. However, the salience of internal social comparison is subject to institutional contingencies. We test these arguments using panel data from 1449 group affiliates in China during the period 2005–12. We find that internal social comparison has a greater effect on a group affiliate's strategic change than does external social comparison. Moreover, this effect differential is smaller in groups located in regions with more developed market institutions but larger in state‐owned groups and groups managed by internally promoted CEOs.